Parenting Education Intervention on the Growth and Development of Stunted Toddlers in the Puskesmas Fakfak Area, West Papua Province - Fretes, Elzina Dina De; Atanai, Yosina (Science Midwifery, 2024)
Background: Stunting remains a critical public health issue in Indonesia, particularly in remote areas such as the Puskesmas Fakfak area, West Papua Province. Stunting, which results from chronic malnutrition, affects the physical and cognitive development of children. Effective strategies to combat stunting are needed, focusing on improving parental knowledge, attitudes, and behaviors regarding child nutrition and care practices. Objectives: This study aims to evaluate the effectiveness of educational interventions in improving the knowledge, attitudes, and behaviors of parents in supporting the growth and development of stunted toddlers in the Puskesmas Fakfak area, West Papua Province. Methods: The research method employed was quasi-experimental with a pre-test and post-test design. The educational intervention consisted of counseling sessions and focused group discussions covering topics such as nutrition, the importance of exclusive breastfeeding, and proper parenting practices. Results: The results of the study indicated a significant increase in parental knowledge, with the average score rising from 3.5 before the intervention to 4.8 after the intervention (t = 7.89, p < 0.001). Parents also demonstrated a positive change in attitudes, as evidenced by an increase in the average score from 3.6 to 4.9 (t = 8.12, p < 0.001). Furthermore, parental behaviors showed a significant improvement, with the average score increasing from 3.4 to 4.8 (t = 7.65, p < 0.001). Conclusion: This research highlights the effectiveness of educational interventions in enhancing parental knowledge, attitudes, and behaviors, which, in turn, can contribute to the mitigation of stunting. It is recommended that similar programs be implemented in other areas facing stunting issues and that longitudinal studies be conducted to assess the sustainability of the interventions' impact.